2019
DOI: 10.1002/rra.3510
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐annual contemporary flood event overbank sedimentation within the vegetated lower Orinoco floodplain, Venezuela

Abstract: Multi‐annual contemporary flood event overbank sedimentation rates were quantified on the World's third largest river in terms of discharge, the tropical lower Orinoco. We discuss the role of variables at the basin and reach scales that contributed to the complexity of spatio‐temporal overbank sediment deposition patterns. Monitored in situ plots were characterized by distance to the main channel, hydroperiod, different geomorphological units, and vegetation cover. Flood event sedimentation rates showed a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Medians ± median absolute deviations (MAD) of basic parameters of the topsoil and the subsoil for the plots situated along the cross-sectional transect of the park (Figure 3), (0.00 = < 0.005) and 93-95%, respectively. Thus, the accumulation processes of various grain sized sediments in the park were affected both by local geomorphology and by the type of vegetation, as also published in other studies (Thonon et al 2007, Rodríguez et al 2019.…”
Section: Resultssupporting
confidence: 69%
“…Medians ± median absolute deviations (MAD) of basic parameters of the topsoil and the subsoil for the plots situated along the cross-sectional transect of the park (Figure 3), (0.00 = < 0.005) and 93-95%, respectively. Thus, the accumulation processes of various grain sized sediments in the park were affected both by local geomorphology and by the type of vegetation, as also published in other studies (Thonon et al 2007, Rodríguez et al 2019.…”
Section: Resultssupporting
confidence: 69%
“…In the same three plots the sedimentation, especially underneath the vegetation, was still reasonably high (19.65 -66.85 mg m -2 [overall median 60.55 mg m -2 ]), which is in contrast with other studies that found exponential decreasing sedimentation rates on horizontal lines in the floodplain (70,71). Also other studies found decreasing amounts of sediment with increasing straight distance from the river (27,29,40,72), with increasing flow path (42) and with decreasing hydrological connectivity (15,43,44). Our result show the substantial role of shallow sites, such as abandoned meander and depression within the floodplain for sediment retention.…”
Section: Topographymentioning
confidence: 56%
“…Such a measure for the true 'hydrological distance' may thus better represent the topography of the floodplain. Some studies used other terms to describe a similar measure such as the flow path (41,42) or the hydrological connectivity (15,43,44). The aim of this study was a holistic analysis putting vegetation and topography control in perspective by first disentangling sedimentation on and underneath the vegetation under in situ conditions, second by quantifying the relative importance of vegetation characteristics in relation to topographical parameter and third, by investigated the effects of additional vegetation characteristics (species diversity and leaf surface structure) on sedimentation within a vegetation patch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabacchi et al () explore the biogeomorphological succession driven by interactions between plants and physical processes in river corridors, specifically highlighting the importance of species composition and plant traits. Rodríguez et al () also consider interactions between plants and sediments that give rise to patterns of overbank sedimentation within the lower Orinoco floodplain. Finally, Javernick and Bertoldi () present the results of experimental flume research designed to investigate how gravel‐bed braided rivers naturally control vegetation encroachment through morphological processes and the impact of both naturally‐occurring and induced avulsions on those processes.…”
Section: Special Issue Papersmentioning
confidence: 99%